MENGGALI NILAI-NILAI PENDIDIKAN AKHLAK DALAM AJARAN TASAWUF - Mustang, Abubakar (STAI YAPIS Takalar, 2022)
In principle, Sufism is a manifestation of the value of ihsan, carrying out devotion to Allah swt. as if seeing Him, and with it Allah Himself witnesses who performs service to Him. Since the beginning of its emergence, Sufism which is still in the form of zuhud life to its development which gives birth to various color patterns, there is a common thread which is a point of similarity between one style of Sufism with other Sufism styles, namely the effort to instill al-Karimah character in a Sufi through efforts. the maximum, step by step to get closer to Allah swt., including the attitude of wara', zuhud, mahabbah, sincere, and qana'ah. This attitude is expected to be a driving force for human service on this earth, devotion needs to be accompanied by sincerity, strong cooperation on the joints of love and mutual respect, devotion must be carried out with full caution, dedication will certainly produce results, and the maximum results are grateful for, while the results that have not been maximized become the motivation to improve further in the next step.